Miracle Mangroves: Funding of green shields in the Bay of Bengal - SCHILLEBEECKX, Simon J.D. (Institutional Knowledge at Singapore Management University, 2018)
The case captures the story of Worldview International Foundation (WIF), focusing especially in the 2012–2016 period during which the organisation started to restore and develop a mangrove forest in the Bay of Bengal on the west coast of Myanmar. The story focuses on the decision-making processes and choices that WIF’s chief executive officer Arne Fjørtoft has to take. In 2012, Fjørtoft secures funding from the Letten Foundation in Norway for a three-year research project in Myanmar on mangrove restoration. While his initial project description was simply to start planting mangrove trees for carbon sequestration, the project was redesigned as a research project to align with the new rules the Letten Foundation had to follow. Fjørtoft decides to embark on a two and a half year journey in order to scale the operation within and beyond Myanmar. For this however, he needs funding. Obtaining that funding is the key objective we focus on. The case ends with the students being presented with three alternative options: (a) Kick-start the collaboration with Alan Laubsch from Lykke on the blockchain cryptocurrency called TREE; (b) Pursue Voluntary Carbon Standard accreditation in the hope that WIF could start selling carbon credits to organisations globally; (c) Try another grant application to either the Global Climate Fund or the Norwegian Ministry for Environment and Climate, this time with the help of the United Nations Environment Programme as the accredited agency. NGOs are complex organisations that interact with many stakeholders, and managing an NGO can be even more complex than managing a profit-seeking company. The importance of good leadership and social capital are underlined.